Realistic Interpretation of Quantum Mechanics - Santos Corchero, Emilio (Cambridge Scholars Publishing, 2022)
According to Einstein ""a physical theory should offer a picture of reality"". This made him frustrated and dissatisfied with the standard interpretation (or lack thereof) of quantum theory, since attempts to get a ""picture"" from it soon led to contradictions like the wave-particle duality. This book provides such a picture of the quantum world, that is, a ""realistic interpretation"". Of course, this needs to be done in a way that is compatible with today's experimental evidence, including the experiments that seem to contradict (local) realism.The book also offers a personal view on the me.